A new basin depth map of the fault-bound Wellington CBD based on residual gravity anomalies. Issue 1 (2nd January 2023) - Stronach, Alistair; Stern, Tim
ABSTRACT: A new basin depth map for the Wellington Central Business District shows a maximum depth of 540 m near the Wellington Stadium. Our new basin geometry constraints are from a residual gravity anomaly study, based on ∼600 new gravity observations. Residual gravity anomalies are as large as −6.2 mGal with uncertainties <0.1 mGal. Two-dimensional gravity models constrained by boreholes that intersect basement are used to generate the basin depth map. Our maximum depth is twice that previously estimated from other geological and geophysical criteria. An onshore extension of the recently discovered Aotea Fault on the western side of Mt Victoria, is also interpreted from the gravity data. A maximum basement offset of up to 130 m and gravity anomaly gradients up to 8 mGal/km are observed across the fault. A secondary splay off the main Aotea Fault is identified in the NW corner of Mt Victoria, and a possible extension to the Lambton Fault is identified beneath the Wellington Railway Station. This new basin depth and fault trace data provide valuable constraints to models of seismic hazard assessment for Wellington City.